Evidence for C and Mg variations in the GD-1 stellar stream. Issue 4 (11th July 2022) - Balbinot, Eduardo; Cabrera-Ziri, Ivan; Lardo, Carmela
ABSTRACT: Dynamically cold stellar streams are the relics left over from globular cluster dissolution. These relics offer a unique insight into a now fully disrupted population of ancient clusters in our Galaxy. Using a combination of Gaia eDR3 proper motions, optical and near-UV colours, we select a sample of likely Red Giant Branch stars from the GD-1 stream for medium-low resolution spectroscopic follow-up. Based on radial velocity and metallicity, we are able to find 14 new members of GD-1, 5 of which are associated with the spur and blob/cocoon off-stream features. We measured C-abundances to probe for abundance variations known to exist in globular clusters. These variations are expected to manifest in a subtle way in globular clusters with such low masses (10^4 M_ ) and metallicities ([Fe/H] ∼ −2.1 dex). We find that the C-abundances of the stars in our sample display a small but significant (3σ level) spread. Furthermore, we find ∼3σ variation in Mg-abundances among the stars in our sample that have been observed by APOGEE. These abundance patterns match the ones found in Galactic globular clusters of similar metallicity. Our results suggest that GD-1 represents another fully disrupted low-mass globular cluster where light-element abundance spreads have been found.